2017
DOI: 10.3233/nre-162102
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency tests: Developing a new model of administration and scoring for Spanish language

Abstract: This review showed that still there is no consensus regarding the administration and scoring of VFT. A new method of administration and scoring is presented that can be use with Spanish-speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…With this approach, the test can be applied to children who have not consolidated their spelling knowledge and to adults with no education (Olabarrieta-Landa et al, 2017). Other authors such as Beltrán Dulcey and Solís Uribe (2012) also used the / f /, / a /, / s / phonemes when applying the test to a number of Colombian adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, the test can be applied to children who have not consolidated their spelling knowledge and to adults with no education (Olabarrieta-Landa et al, 2017). Other authors such as Beltrán Dulcey and Solís Uribe (2012) also used the / f /, / a /, / s / phonemes when applying the test to a number of Colombian adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Within research and clinical practice, the most commonly used verbal fluency tests are phonological and semantic (Strauss et al, 2006;Marino and Alderete, 2010;Lezak, 2012). Phonological fluency requires executive functioning and the activation of areas within the frontal lobe, whereas semantic fluency taps into lexical access and vocabulary and requires participation of the temporal lobe (Olabarrieta-Landa et al, 2017). The assessment of this test must comply with certain rules including time limits for word generation, instructions about the types of words that must be evoked and/or omitted, and specific scoring guidelines (Olabarrieta-Landa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several variables that may impact letter verbal fluency, which were not assessed in this study, could explain these differences in scores among countries. For instance, language-related competences (e.g., vocabulary level, reading, and writing) have been associated with better performance in letter verbal fluency (Kochhann, Holz, Beber, Chaves, & Fonseca, 2018; Olabarrieta-Landa, Rivera, et al, 2017; Olabarrieta-Landa, Torre, et al, 2017). In countries with bilingual population, such as Puerto Rico, bilingualism might be an important variable since it has been also related to letter verbal fluency, with no clear results: While some studies have reported that monolinguals outperform bilingual participants on letter verbal fluency (Bialystok, Craik, & Luk, 2008; Gollan, Montoya, & Werner, 2002), others have found that bilingual participants outperform monolinguals when vocabulary level is similar among both groups (Friesen, Luo, Luk, & Bialystok, 2015; Luo, Luk, & Bialystok, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were required to produce as many words as possible in 1 minute beginning with the letters M, R, and P. The VFTs were always administered in the same order, that is, first letter M, subsequently letter R, and finally letter P. For administration and scoring, the guidelines of Olabarrieta-Landa, Rivera, et al (2017) and Olabarrieta-Landa, Torre, et al (2017) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation